Identifying priority agricultural value chains in Senegal - Randriamamonjy, Josee; Thurlow, James; Wiebelt, Manfred (PEGNet, 2020)
In developing countries, where agriculture is a major economic sector, value-chain development is expected to contribute to high-level outcomes. In this paper, we aim at quantitatively assessing the value-chains which will be the most effective at fostering national and regional economic development along four dimensions: generating economic growth in the agricultural-food sector; reducing national and rural poverty; creating employment; and improving nutrition by diversifying diets. We propose an economywide systems-approach using a spatially-disaggregated dynamic computable general equilibrium model that we apply to Senegal. Simulation results indicate that fishery is the most effective value chain at generating growth in the regions with potential for fishery expansion (Thies-Diourbel, the Northern, and the Southern regions). Rice is the first value chain to reduce poverty in the Northern and Southern regions where irrigated and rainfed rice cultivation respectively dominate. Growth led by the fruits sector is the most effective at improving nutrition in all four regions where fruits are grown (Thies-Diourbel, the Northern, Central, and Southern regions).